Nutrient uptake, quality, water expanse components and economics of cowpea as influenced by fertility levels and mulching - Choudhary, S.K.; Shivran, A.C.; Choudhary, G.L.; Prajapat, K. (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif, 2010 on a loamy sand soil to investigate the effect of fertility levels along with moisture conservation practices on nutrient uptake, quality, water expanse components and economics of cowpea. Results indicated that total uptake of N and P, protein content in seed, relative leaf water content and net returns increased significantly with 100% RDF over control and 50% RDF but remained at par with 75% RDF. Whereas, application of fertilizers up to 100% RDF recorded significantly higher water expense efficiency over its preceding levels. Results further indicated that all the mulches remained almost similar with each other and significantly superior to control in terms of total uptake of N and P, protein content in seed, relative leaf water content, profile water depletion, total water expense and water expense efficiency. However, application of straw mulch fetched significantly higher net returns over control and plastic mulch but remained at par with dust mulch.